Hypertension and Cardiovascular Risk Factors in Young University Students from Quito, Ecuador - Ruano Nieto CI; Melo Perez JD; Mogrovejo Freire LE; De Paula Morales KR; Espinoza Romero CV (Archives of Clinical Hypertension - Peertechz Publications, 2015)
Introduction: Hypertension is the most common chronic non-contagious disease. High blood pressure is an important risk factor for premature mortality and contributes to the development of heart disease, stroke and kidney failure. In spite of the fact that it is consider to be an adult disease, the frequency in young people has increased. Methods: All students enrolled in first, second and third semester of the Medical School, Faculty of Medical Sciences - Universidad Central del Ecuador, period October 2014 - March 2015 were invited to participate. Body mass index was calculated; waist circumference and blood pressure were measured. The diagnosis of hypertension was made using recommended criteria by the ATP III, IDF and JNC 7. Blood chemistry including urea, glucose, creatinine, uric acid and lipid profile were determined. Results: 883 college students in a range of 17-25 years were included; the average age was 19.3 ± 1.4 (63.3% female and 36.7% male). 15.2% (n = 134) presented a blood pressure >130/85, 9.51% (n = 84) had elevated systolic pressure and 9.1% (n = 81) elevated diastolic pressure. 33.9% had rehypertension. 22.3% (n = 197) were overweight and 3.2% (n = 28) obese. In students with altered waist circumference, it was tendency to increase systolic and diastolic blood pressure: Hypertriglyceridemia (> 150 mg / dl) is associated with high systolic blood pressure.Conclusion: Body mass index, waist circumference and male gender were associated with an increase in both, systolic and diastolic blood pressure in young university students.